Karakteristik Lahan Untuk Tanaman Melon (Cucumis Melo L.) dalam Kaitannya Dengan Peningkatan Kadar Gula - Ir, MT., Siswanto; Dr. Ir, MP., Bakti Wisnu W; Ir, MP., Purwadi (MAPETA, 2010)
The experimental was conducted in randomized block design and three replication with three factor. First factor was fertilize cage with dose 0 tonha-1, 10 tonha-1, 20 tonha-1 and 30 tonha-1. Second factor was fertilize KCl with dose 175 kgha-1, 200 kgha-1and 225 kgha-1. Three factor dolomit with dose 100 kgha-1, 125 kgha-1and 150 kgha-1. Result showed that addition fertilize Cage, fertilize KCl and Dolomit by signifikan on weight fruit, sugar content, and fibre of melon. Rate of weight with mean 1.82 kg. Rate of highest Heavy at treatment B3K2CM3 (2.30 kg) and lowered at treatment B1K3CM2 (1.20 kg). Rate of sugar with mean 10.47% and rate of fibre with mean 9.86%. Rate of highest Sugar at treatment B3K3CM3 (13.44%) and lowered at treatment of B1K2CM2 of equal to 7.20%. rate of highest fibre at treatment B4K1CM3 (11.72%). and lowerwd at treatment of B2K1CM2 of equal to 7.78%. Use fertilize cage with dose 20 kgha-1, fertilize KCL 200 kgha-1and dolomit 150 kgha-1 have an effect on to fruit quality of melons.Key Word: Land Characteristic, Sugar Content